1998
DOI: 10.1137/s0097539796306474
|View full text |Cite
|
Sign up to set email alerts
|

A Downward Collapse within the Polynomial Hierarchy

Abstract: Downward collapse (a.k.a. upward separation) refers to cases where the equality of two larger classes implies the equality of two smaller classes. We provide an unqualified downward collapse result completely within the polynomial hierarchy. In particular, we prove that, for k > 2, if PWe extend this to obtain a more general downward collapse result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Then we will have either the first or second column accepting respectively. ¾ Hemaspaandra, Hemaspaandra and Hempel [HHH99a] give a more general version of Theorem 3.1 for the boolean hierarchy over ¦ Ô for ¾. In a later paper, Hemaspaandra, Hemaspaandra and Hempel [HHH99b] show that our Theorem 3.2 similarly extends to the boolean hierarchy over ¦ Ô ¾ .…”
Section: Claim 34 the Algorithm Inmentioning
confidence: 74%
See 2 more Smart Citations
“…Then we will have either the first or second column accepting respectively. ¾ Hemaspaandra, Hemaspaandra and Hempel [HHH99a] give a more general version of Theorem 3.1 for the boolean hierarchy over ¦ Ô for ¾. In a later paper, Hemaspaandra, Hemaspaandra and Hempel [HHH99b] show that our Theorem 3.2 similarly extends to the boolean hierarchy over ¦ Ô ¾ .…”
Section: Claim 34 the Algorithm Inmentioning
confidence: 74%
“…Easy-III are formulas with a short proof of nonsatisfiability given that they failed to be Easy-II. Easy-IV strings are formulas with a short proof of nonsatisfiability using techniques from Hemaspaandra, Hemaspaandra and Hempel [HHH99a] discussed in Section 3.…”
Section: Beigel Chang and Ogihara [Bco93] Building On Work Of Chang mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent results [1,8,17,18] brought the collapse further down, to within ∆ P 3 . A breakthrough in the proof techniques came when Hemaspaandra, Hemaspaandra and Hempel [13] showed that if the queries were made to a Σ P 3 oracle (instead of SAT), then PH ⊆ Σ P 3 which is a downward collapse. Buhrman and Fortnow [2] improved this technique and made it work for queries to a Σ P 2 oracle.…”
Section: Introductionmentioning
confidence: 99%
“…For technical reasons that we will not go into here, the case of one query versus two queries is a special case. By considering whether the input string itself might be a hard string, downward collapses can be achieved for queries to Σ P i for i ≥ 2 [10,6]: P Σ P i [1] = P Σ P i [2] ⇐⇒ PH ⊆ Σ P i .…”
Section: Introductionmentioning
confidence: 99%